Anti-aging vehicle natural gas catalyst and preparation method thereof

By adding high-nickel oxide to the coating material of natural gas catalysts and combining other oxides and precious metals, the problem of catalyst coating aging is solved, and the anti-aging performance and durability of the catalyst is significantly improved, meeting the requirements of the National VI standard.

CN119455979APending Publication Date: 2025-02-18WUXI WEIFU ENVIRONMENT PROTECTION CATALYST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411750049.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The coating deterioration of existing natural gas catalysts under long-term high temperature conditions, resulting in poor durability and inability to meet the National VI standard. How to improve the anti-aging ability of the catalyst is a difficult problem.

Method used

High nickel oxide is added to the coating material, and anti-aging automotive natural gas catalyst is prepared by combining aluminum oxide, Ce-Zr composite oxide and precious metals (such as Pd, Rh, Pt).

Benefits of technology

Effectively improve the anti-aging performance of the catalyst coating, slow down sintering, avoid embedding of precious metals, maintain the catalytic capacity after aging, and meet the durability requirements of the National VI standard.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005164781160000061
    Figure BDA0005164781160000061
Patent Text Reader

Abstract

The invention provides an anti-aging vehicle natural gas catalyst, which comprises a carrier, a lower coating coated on the carrier and an upper coating coated on the lower coating, each of the lower coating and the upper coating comprises a coating material and a noble metal loaded on the coating material, the coating material comprises alumina, a Ce-Zr composite oxide and nickelic oxide, and the noble metal is loaded on the coating material. The noble metal of the lower coating is Pd, the noble metal of the upper coating is Rh, and the upper coating and / or the lower coating further comprise noble metal Pt. According to the anti-aging vehicle natural gas catalyst and the preparation method thereof, high nickel oxide is introduced into a coating material of the catalyst, so that sintering of a catalyst coating can be slowed down, and the problem of precious metal embedding caused by structural collapse after the catalyst coating is aged can be effectively solved; the problem that the catalytic ability of the aged catalyst to nitrogen oxide and methane is greatly reduced is solved, so that the anti-aging performance of a catalyst coating can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to an anti-aging type natural gas catalyst for vehicles and a preparation method thereof. Background Art

[0002] With the continuous development of global science and technology, the use of fossil fuels has involved all aspects of human life. In ancient times, people traveled by horse, but now people travel by car, ship, and airplane, truly traveling thousands of miles a day. While enjoying this convenience, the pollution caused by fossil fuels has become an inevitable environmental problem.

[0003] By installing a catalytic purifier device at the exhaust outlet of a motor vehicle that can catalytically purify exhaust pollutants, the content of pollutant gases emitted in the exhaust gas of the motor vehicle can be effectively reduced. In this way, the air can be effectively purified and the environment can be protected.

[0004] Compared with gasoline and diesel engines, the pollutant gases produced by gas engines, i.e. natural gas engines, are mainly methane, nitrogen oxides, and carbon monoxide, but the total emission of harmful substances is much lower than that of gasoline and diesel engines; nowadays, with the continuous tightening of national regulations, the limits of pollutants are constantly decreasing, and the requirements for catalysts are getting higher and higher. The National VI standard has made clear provisions on the durability of catalysts; the degradation of catalyst coatings under long-term high temperature conditions is a problem, which leads to the deterioration of the durability of the catalyst, and it may even fail to meet the National VI standard. Therefore, how to improve the anti-aging ability of the catalyst is the direction of catalyst progress. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies in the prior art and provide an anti-aging type vehicle natural gas catalyst and a preparation method thereof. To address the problem of coating degradation, the present invention adds high nickel oxide to the coating material, which can effectively improve the anti-aging performance of the catalyst coating.

[0006] The technical solution adopted by the present invention is:

[0007] An anti-aging type natural gas catalyst for vehicles, comprising a carrier, a lower coating layer coated on the carrier, and an upper coating layer coated on the lower coating layer, wherein the lower coating layer and the upper coating layer both comprise a coating material and a precious metal loaded on the coating material, the coating material comprises aluminum oxide, Ce-Zr composite oxide, and nickel oxide, the precious metal of the lower coating layer is Pd, the precious metal of the upper coating layer is Rh, and the upper coating layer and / or the lower coating layer further comprises the precious metal Pt.

[0008] Preferably, in the anti-aging type natural gas catalyst for vehicles, the coating amount of the lower coating layer is 80-200 g / L, and the coating amount of the upper coating layer is 50-180 g / L.

[0009] Preferably, in the anti-aging vehicle natural gas catalyst, the noble metal of the upper coating is Rh, the noble metal of the lower coating is Pd, the Pt is distributed in the upper coating and / or the lower coating, and the loading amount of Rh is 0.1 to 15 g / ft 3 , Pd loading is 0.5~150g / ft 3 , Pt loading is 0.5~200g / ft 3 .

[0010] Preferably, in the anti-aging type natural gas catalyst for vehicles, the carrier is a cordierite honeycomb ceramic carrier with a mesh size of 300 to 600 meshes and a wall thickness of 3 to 6 mils.

[0011] Preferably, in the anti-aging type natural gas catalyst for vehicles, the alumina is γ-alumina with a specific surface area of ​​200 to 250 m 2 / g.

[0012] Preferably, in the anti-aging vehicle natural gas catalyst, the Ce-Zr composite oxide is a cerium-zirconium solid solution, and the Ce-Zr composite oxide comprises 30-70% cerium oxide and 30-70% zirconium oxide by mass percentage.

[0013] Preferably, in the anti-aging type natural gas catalyst for vehicles, the mass ratio of the aluminum oxide, the Ce-Zr composite oxide and the nickel oxide is 10:6:1-5.

[0014] The present invention also provides a method for preparing an anti-aging vehicle natural gas catalyst, which comprises the following steps:

[0015] (1) Undercoat coating: Alumina, Ce-Zr composite oxide and high nickel oxide are prepared into a raw slurry in a mass ratio of 10:6:1-5 and stirred, and then a precursor solution containing precious metal Pd or a precursor solution containing precious metal Pd and precious metal Pt is added to the raw slurry, stirred for 0.5 to 2 hours to obtain a lower coating slurry, and then the lower coating slurry is coated on the catalyst carrier, and dried and calcined to obtain a semi-finished catalyst;

[0016] (2) Top coating coating: Alumina, Ce-Zr composite oxide and nickel oxide are prepared into a slurry in a mass ratio of 10:6:1-5 and stirred. Subsequently, a precursor solution containing precious metal Rh or a precursor solution containing precious metal Rh and precious metal Pt is added to the slurry and stirred for 0.5 to 2 hours to obtain a top coating slurry. The top coating slurry is coated on the semi-finished catalyst obtained in step (1), and dried and calcined to obtain a finished catalyst.

[0017] Preferably, in the method for preparing the anti-aging vehicle natural gas catalyst, the precursor of Pd is selected from one of tetraamminepalladium nitrate, chloropalladic acid, and palladium nitrate; the precursor of Rh is selected from one of rhodium nitrate, rhodium chloride, and rhodium acetylacetonate; and the precursor of Pt is selected from one of dinitrosodiammineplatinum, tetraammonium platinum dichloride, chloroplatinic acid, and platinum nitrate.

[0018] Preferably, in the method for preparing the anti-aging vehicle natural gas catalyst, the drying temperature in step (1) and step (2) is 180-220°C, the drying time is 2.5-3.5h, the calcination temperature is 550-650°C, and the calcination time is 1.5-2.5h.

[0019] Advantages of the present invention:

[0020] The anti-aging type vehicle natural gas catalyst and the preparation method thereof of the present invention introduces high nickel oxide into the coating material of the catalyst, which can slow down the sintering of the catalyst coating, effectively solve the problem of precious metal embedding caused by structural collapse of the catalyst coating after aging, and slow down the problem of a significant decrease in the catalytic ability of the aged catalyst to nitrogen oxides and methane, thereby effectively improving the anti-aging performance of the catalyst coating DETAILED DESCRIPTION

[0021] The present invention will be further described below in conjunction with specific embodiments.

[0022] Example 1

[0023] An anti-aging vehicle natural gas catalyst comprises a carrier, a lower coating layer coated on the carrier, and an upper coating layer coated on the lower coating layer, wherein the lower coating layer and the upper coating layer both comprise a coating material and a precious metal supported on the coating material, wherein the coating material comprises aluminum oxide, Ce-Zr composite oxide, and nickel oxide, the precious metal of the lower coating layer is Pd, and the precious metal of the upper coating layer is Rh and Pt.

[0024] The coating amount of the lower coating layer is 130 g / L, the coating amount of the upper coating layer is 120 g / L; the Rh loading amount is 3 g / ft 3 , Pd loading is 50g / ft 3 , the Pt loading is 20g / ft 3 The carrier is a cordierite honeycomb ceramic carrier with a mesh size of 400 and a wall thickness of 4 mils; the alumina is γ-alumina with a specific surface area of ​​200 to 250 m 2 / g; the Ce-Zr composite oxide is a cerium-zirconium solid solution, and in terms of mass percentage, the Ce-Zr composite oxide includes 50% cerium oxide and 50% zirconium oxide.

[0025] The method for preparing the anti-aging vehicle natural gas catalyst of this embodiment comprises the following steps:

[0026] (1) Undercoat coating: 2000 g of aluminum oxide, Ce-Zr composite oxide and high nickel oxide were prepared into a raw slurry in a mass ratio of 10:6:1 and stirred, then a palladium nitrate solution with a mass concentration of 10% was slowly added to the raw slurry and stirred for 1 hour to obtain a lower coating slurry, and then the lower coating slurry was coated on the catalyst carrier, and dried and calcined at a drying temperature of 200°C for 3 hours, and a calcination temperature of 650°C for 2 hours to obtain a semi-finished catalyst;

[0027] (2) Top coating coating: 2000 g of aluminum oxide, Ce-Zr composite oxide and nickel oxide are prepared into a slurry in a mass ratio of 10:6:1 and stirred. Subsequently, a 10% by mass concentration of rhodium nitrate solution and a 10% by mass concentration of platinum nitrate solution are slowly added to the slurry and stirred for 1 hour to obtain a top coating slurry. The top coating slurry is coated on the semi-finished catalyst obtained in step (1), and dried and calcined at a drying temperature of 200°C for 3 hours and a calcination temperature of 650°C for 2 hours to obtain a finished catalyst.

[0028] Example 2

[0029] An anti-aging vehicle natural gas catalyst comprises a carrier, a lower coating layer coated on the carrier, and an upper coating layer coated on the lower coating layer, wherein the lower coating layer and the upper coating layer both comprise a coating material and a precious metal supported on the coating material, wherein the coating material comprises aluminum oxide, Ce-Zr composite oxide, and nickel oxide, the precious metal of the lower coating layer is Pd, and the precious metal of the upper coating layer is Rh and Pt.

[0030] The coating amount of the lower coating layer is 130 g / L, the coating amount of the upper coating layer is 120 g / L; the Rh loading amount is 3 g / ft 3 , Pd loading is 50g / ft 3 , the Pt loading is 20g / ft 3 The carrier is a cordierite honeycomb ceramic carrier with a mesh size of 400 and a wall thickness of 4 mils; the alumina is γ-alumina with a specific surface area of ​​200 to 250 m 2 / g; the Ce-Zr composite oxide is a cerium-zirconium solid solution, and in terms of mass percentage, the Ce-Zr composite oxide includes 50% cerium oxide and 50% zirconium oxide.

[0031] The method for preparing the anti-aging vehicle natural gas catalyst of this embodiment comprises the following steps:

[0032] (1) Undercoat coating: 2000 g of aluminum oxide, Ce-Zr composite oxide and high nickel oxide were prepared into a raw slurry in a mass ratio of 10:6:2 and stirred, and then a palladium nitrate solution with a mass concentration of 10% was slowly added to the raw slurry and stirred for 1 hour to obtain a lower coating slurry, and then the lower coating slurry was coated on the catalyst carrier, and dried and calcined at a drying temperature of 200°C for 3 hours, and a calcination temperature of 650°C for 2 hours to obtain a semi-finished catalyst;

[0033] (2) Top coating coating: 2000 g of aluminum oxide, Ce-Zr composite oxide and nickel oxide are prepared into a slurry in a mass ratio of 10:6:2 and stirred. Subsequently, a 10% by mass concentration of rhodium nitrate solution and a 10% by mass concentration of platinum nitrate solution are slowly added to the slurry and stirred for 1 hour to obtain a top coating slurry. The top coating slurry is coated on the semi-finished catalyst obtained in step (1), and dried and calcined at a drying temperature of 200°C for a drying time of 3 hours and a calcination temperature of 650°C for a calcination time of 2 hours to obtain a finished catalyst.

[0034] Example 3

[0035] An anti-aging vehicle natural gas catalyst comprises a carrier, a lower coating layer coated on the carrier, and an upper coating layer coated on the lower coating layer, wherein the lower coating layer and the upper coating layer both comprise a coating material and a precious metal supported on the coating material, wherein the coating material comprises aluminum oxide, Ce-Zr composite oxide, and nickel oxide, the precious metal of the lower coating layer is Pd, and the precious metal of the upper coating layer is Rh and Pt.

[0036] The coating amount of the lower coating layer is 130 g / L, the coating amount of the upper coating layer is 120 g / L; the loading amount of Rh is 3 g / ft 3 , Pd loading is 50g / ft 3 , the Pt loading is 20g / ft 3 The carrier is a cordierite honeycomb ceramic carrier with a mesh size of 400 and a wall thickness of 4 mils; the alumina is γ-alumina with a specific surface area of ​​200 to 250 m 2 / g; the Ce-Zr composite oxide is a cerium-zirconium solid solution, and in terms of mass percentage, the Ce-Zr composite oxide includes 50% cerium oxide and 50% zirconium oxide.

[0037] The method for preparing the anti-aging vehicle natural gas catalyst of this embodiment comprises the following steps:

[0038] (1) Undercoat coating: 2000 g of aluminum oxide, Ce-Zr composite oxide and high nickel oxide were prepared into a raw slurry in a mass ratio of 10:6:3 and stirred, then a palladium nitrate solution with a mass concentration of 10% was slowly added to the raw slurry and stirred for 1 hour to obtain a lower coating slurry, and then the lower coating slurry was coated on the catalyst carrier, and dried and calcined at a drying temperature of 200°C for 3 hours and a calcination temperature of 650°C for 2 hours to obtain a semi-finished catalyst;

[0039] (2) Top coating coating: 2000 g of aluminum oxide, Ce-Zr composite oxide and high nickel oxide are prepared into a slurry in a mass ratio of 10:6:3 and stirred. Subsequently, a 10% by mass concentration of rhodium nitrate solution and a 10% by mass concentration of platinum nitrate solution are slowly added to the slurry and stirred for 1 hour to obtain a top coating slurry. The top coating slurry is coated on the semi-finished catalyst obtained in step (1), and dried and calcined at a drying temperature of 200°C for a drying time of 3 hours and a calcination temperature of 650°C for a calcination time of 2 hours to obtain a finished catalyst.

[0040] Example 4

[0041] An anti-aging vehicle natural gas catalyst comprises a carrier, a lower coating layer coated on the carrier, and an upper coating layer coated on the lower coating layer, wherein the lower coating layer and the upper coating layer both comprise a coating material and a precious metal supported on the coating material, wherein the coating material comprises aluminum oxide, Ce-Zr composite oxide, and nickel oxide, the precious metal of the lower coating layer is Pd, and the precious metal of the upper coating layer is Rh and Pt.

[0042] The coating amount of the lower coating layer is 130 g / L, the coating amount of the upper coating layer is 120 g / L; the loading amount of Rh is 3 g / ft 3 , Pd loading is 50g / ft 3 , the Pt loading is 20g / ft 3 The carrier is a cordierite honeycomb ceramic carrier with a mesh size of 400 and a wall thickness of 4 mils; the alumina is γ-alumina with a specific surface area of ​​200 to 250 m 2 / g; the Ce-Zr composite oxide is a cerium-zirconium solid solution, and in terms of mass percentage, the Ce-Zr composite oxide includes 50% cerium oxide and 50% zirconium oxide.

[0043] The method for preparing the anti-aging vehicle natural gas catalyst of this embodiment comprises the following steps:

[0044] (1) Undercoat coating: 2000 g of aluminum oxide, Ce-Zr composite oxide and high nickel oxide were prepared into a raw slurry in a mass ratio of 10:6:4 and stirred, and then a palladium nitrate solution with a mass concentration of 10% was slowly added to the raw slurry and stirred for 1 hour to obtain a lower coating slurry, and then the lower coating slurry was coated on the catalyst carrier, and dried and calcined at a drying temperature of 200° C. for 3 hours, and a calcination temperature of 650° C. for 2 hours to obtain a semi-finished catalyst;

[0045] (2) Top coating coating: 2000 g of aluminum oxide, Ce-Zr composite oxide and nickel oxide are prepared into a slurry in a mass ratio of 10:6:4 and stirred. Subsequently, a 10% by mass concentration of rhodium nitrate solution and a 10% by mass concentration of platinum nitrate solution are slowly added to the slurry and stirred for 1 hour to obtain a top coating slurry. The top coating slurry is coated on the semi-finished catalyst obtained in step (1), and dried and calcined at a drying temperature of 200°C for 3 hours and a calcination temperature of 650°C for 2 hours to obtain a finished catalyst.

[0046] Example 5

[0047] An anti-aging vehicle natural gas catalyst comprises a carrier, a lower coating layer coated on the carrier, and an upper coating layer coated on the lower coating layer, wherein the lower coating layer and the upper coating layer both comprise a coating material and a precious metal supported on the coating material, wherein the coating material comprises aluminum oxide, Ce-Zr composite oxide, and nickel oxide, the precious metal of the lower coating layer is Pd, and the precious metal of the upper coating layer is Rh and Pt.

[0048] The coating amount of the lower coating layer is 130 g / L, the coating amount of the upper coating layer is 120 g / L; the loading amount of Rh is 3 g / ft 3 , Pd loading is 50g / ft 3 , the Pt loading is 20g / ft 3 The carrier is a cordierite honeycomb ceramic carrier with a mesh size of 400 and a wall thickness of 4 mils; the alumina is γ-alumina with a specific surface area of ​​200 to 250 m 2 / g; the Ce-Zr composite oxide is a cerium-zirconium solid solution, and in terms of mass percentage, the Ce-Zr composite oxide includes 50% cerium oxide and 50% zirconium oxide.

[0049] The method for preparing the anti-aging vehicle natural gas catalyst of this embodiment comprises the following steps:

[0050] (1) Undercoat coating: 2000 g of aluminum oxide, Ce-Zr composite oxide and high nickel oxide were prepared into a raw slurry in a mass ratio of 10:6:5 and stirred, then a palladium nitrate solution with a mass concentration of 10% was slowly added to the raw slurry and stirred for 1 hour to obtain a lower coating slurry, and then the lower coating slurry was coated on the catalyst carrier, and dried and calcined at a drying temperature of 200° C. for 3 hours, and a calcination temperature of 650° C. for 2 hours to obtain a semi-finished catalyst;

[0051] (2) Top coating coating: 2000 g of aluminum oxide, Ce-Zr composite oxide and nickel oxide are prepared into a slurry in a mass ratio of 10:6:5 and stirred. Subsequently, a 10% by mass concentration of rhodium nitrate solution and a 10% by mass concentration of platinum nitrate solution are slowly added to the slurry and stirred for 1 hour to obtain a top coating slurry. The top coating slurry is coated on the semi-finished catalyst obtained in step (1), and dried and calcined at a drying temperature of 200°C for a drying time of 3 hours and a calcination temperature of 650°C for a calcination time of 2 hours to obtain a finished catalyst.

[0052] Comparative Example 1

[0053] An anti-aging vehicle natural gas catalyst comprises a carrier, a lower coating layer coated on the carrier, and an upper coating layer coated on the lower coating layer, wherein the lower coating layer and the upper coating layer both comprise a coating material and a precious metal supported on the coating material, wherein the coating material comprises aluminum oxide and a Ce-Zr composite oxide, the precious metal of the lower coating layer is Pd, and the precious metal of the upper coating layer is Rh and Pt.

[0054] The coating amount of the lower coating layer is 130 g / L, the coating amount of the upper coating layer is 120 g / L; the Rh loading amount is 3 g / ft 3 , Pd loading is 50g / ft 3 , the Pt loading is 20g / ft 3 The carrier is a cordierite honeycomb ceramic carrier with a mesh size of 400 and a wall thickness of 4 mils; the alumina is γ-alumina with a specific surface area of ​​200 to 250 m 2 / g; the Ce-Zr composite oxide is a cerium-zirconium solid solution, and in terms of mass percentage, the Ce-Zr composite oxide includes 50% cerium oxide and 50% zirconium oxide.

[0055] The preparation method of the anti-aging vehicle natural gas catalyst of this comparative example comprises the following steps:

[0056] (1) Undercoat coating: 2000 g of aluminum oxide and Ce-Zr composite oxide were prepared into a raw slurry in a mass ratio of 10:6 and stirred, and then a 10% mass concentration of palladium nitrate solution was slowly added to the raw slurry and stirred for 1 hour to obtain a lower coating slurry, and then the lower coating slurry was coated on the catalyst carrier, and dried and calcined at a drying temperature of 200° C. for 3 hours, and a calcination temperature of 650° C. for 2 hours to obtain a semi-finished catalyst;

[0057] (2) Top coating coating: 2000 g of aluminum oxide and Ce-Zr composite oxide are prepared into a slurry in a mass ratio of 10:6 and stirred. Subsequently, a 10% rhodium nitrate solution and a 10% platinum nitrate solution are slowly added to the slurry and stirred for 1 hour to obtain a top coating slurry. The top coating slurry is coated on the semi-finished catalyst obtained in step (1), and dried and calcined at a drying temperature of 200°C for 3 hours and a calcination temperature of 650°C for 2 hours to obtain a finished catalyst.

[0058] The catalyst samples prepared in Examples 1-5 and Comparative Example 1 were tested for catalytic performance. The specific testing method is as follows: under the same experimental conditions, the pollutant ignition temperature (T50) of the fresh catalyst and the aged catalyst was tested respectively, wherein the aged catalyst was obtained by aging in an aging furnace with 10% H2O at 1000°C for 10 hours. The lower the T50, the higher the pollutant conversion capacity of the catalyst. The testing experiment was carried out on a Fourier infrared tester. The reaction gas was mixed uniformly in a gas mixing tank in advance. The components in the reaction gas included 0.5% CO, 0.3% H2, 4.5% H2O, 8% CO2, 3000ppm NO and 1200ppm CH4 by volume fraction. N2 was used as the balance gas in the reaction tube, and then O2 was introduced into the reaction tube to adjust the size of λ. In the experiment, λ was stabilized at 0.99. The total gas flow rate during the experiment was GHSV=60000h. -1 , the heating rate is 25℃ / min, the gas flow is measured by an FTIR gas analyzer (MultiGas6030) and controlled by a mass flow controller; wherein, λ refers to the excess air coefficient, that is, the ratio of the actual amount of air supplied to fuel combustion to the theoretical amount of air; when λ=1, the fuel is just completely burned; when λ<1, the fuel cannot be fully burned; when λ>1, there is excess air. The comparison of the ignition temperature of the pollutants in Examples 1-5 and Comparative Example 1 is shown in Table 1.

[0059] Table 1

[0060]

[0061] From the comparison results of the ignition temperature of pollutants in Examples 1-5 and Comparative Example 1 in Table 1, it can be seen that:

[0062] The CH4 and NOx ignition temperatures of the fresh catalyst in Example 1 are 3°C and 2°C lower than those in Comparative Example 1, respectively, and are 23°C and 14°C lower after furnace aging; the CH4 and NOx ignition temperatures of the fresh catalyst in Example 2 are 1°C lower and 1°C higher than those in Comparative Example 1, respectively, and are 31°C and 25°C lower after furnace aging; the CH4 and NOx ignition temperatures of the fresh catalyst in Example 3 are 2°C and 0°C lower than those in Comparative Example 1, respectively, and are 39°C and 33°C lower after furnace aging; the CH4 and NOx ignition temperatures of the fresh catalyst in Example 4 are 0°C and 1°C lower than those in Comparative Example 1, respectively, and are 27°C and 28°C lower after furnace aging; the CH4 and NOx ignition temperatures of the fresh catalyst in Example 5 are 2°C and 1°C higher than those in Comparative Example 1, respectively, and are 16°C and 16°C lower after furnace aging.

[0063] From the above data comparison, it can be seen that in the data comparison between Examples 1-5 and Comparative Example 1, the catalysts prepared by adding high nickel oxide in Examples 1-5 and the catalyst prepared in Comparative Example 1 have equivalent ignition temperatures in the fresh state, and the ignition temperatures of the CH4 and NOx catalysts in Examples 1-5 after furnace aging are lower. At the same time, as the proportion of added high nickel oxide in the total coating increases, the corresponding CH4 and NOx ignition temperatures after aging show a trend of first increasing and then decreasing. When preparing the catalyst, an appropriate amount of high nickel oxide is added to the coating, which greatly improves the anti-aging ability of the catalyst and effectively solves the problem of rapid performance degradation after aging.

[0064] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. An anti-aging vehicle natural gas catalyst, characterized in that: The invention comprises a carrier, a lower coating layer coated on the carrier and an upper coating layer coated on the lower coating layer, wherein the lower coating layer and the upper coating layer both comprise a coating material and a precious metal loaded on the coating material, wherein the coating material comprises aluminum oxide, Ce-Zr composite oxide and high nickel oxide, the precious metal of the lower coating layer is Pd, the precious metal of the upper coating layer is Rh, and the upper coating layer and / or the lower coating layer further comprises the precious metal Pt.

2. The anti-aging type natural gas catalyst for vehicles according to claim 1, characterized in that: The coating amount of the lower coating layer is 80-200 g / L, and the coating amount of the upper coating layer is 50-180 g / L.

3. The anti-aging type natural gas catalyst for vehicles according to claim 1, characterized in that: The loading amount of Rh is 0.1~15g / ft 3 , Pd loading is 0.5~150g / ft 3 , Pt loading is 0.5~200 g / ft 3 .

4. The anti-aging type natural gas catalyst for vehicles according to claim 1, characterized in that: The carrier is a cordierite honeycomb ceramic carrier with a mesh size of 300-600 meshes and a wall thickness of 3-6 mils.

5. The anti-aging type natural gas catalyst for vehicles according to claim 1, characterized in that: The alumina is γ-alumina with a specific surface area of ​​200-250m 2 / g.

6. The anti-aging type natural gas catalyst for vehicles according to claim 1, characterized in that: The Ce-Zr composite oxide is a cerium-zirconium solid solution, and in terms of mass percentage, the Ce-Zr composite oxide includes 30-70% of cerium oxide and 30-70% of zirconium oxide.

7. The anti-aging type natural gas catalyst for vehicles according to claim 1, characterized in that: The mass ratio of the aluminum oxide, Ce-Zr composite oxide and nickel oxide is 10:6:1-5.

8. The method for preparing an anti-aging vehicle natural gas catalyst according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Undercoat coating: Alumina, Ce-Zr composite oxide and high nickel oxide are prepared into a raw slurry in a mass ratio of 10:6:1-5 and stirred, and then a precursor solution containing precious metal Pd or a precursor solution containing precious metal Pd and precious metal Pt is added to the raw slurry, stirred for 0.5-2h to obtain a lower coating slurry, and then the lower coating slurry is coated on the catalyst carrier, and dried and calcined to obtain a semi-finished catalyst; (2) Top coating: Alumina, Ce-Zr composite oxide and nickel oxide are prepared into a slurry in a mass ratio of 10:6:1-5 and stirred. A precursor solution containing precious metal Rh or a precursor solution containing precious metal Rh and precious metal Pt is then added to the slurry and stirred for 0.5-2 hours to obtain a top coating slurry. The top coating slurry is coated on the semi-finished catalyst obtained in step (1), and dried and calcined to obtain a finished catalyst.

9. The method for preparing the anti-aging vehicle natural gas catalyst according to claim 8, characterized in that: The precursor of Pd is selected from one of tetraamminepalladium nitrate, chloropalladic acid, and palladium nitrate; the precursor of Rh is selected from one of rhodium nitrate, rhodium chloride, and rhodium acetylacetonate; the precursor of Pt is selected from one of dinitrosodiammineplatinum, tetraammonium platinum dichloride, chloroplatinic acid, and platinum nitrate.

10. The method for preparing the anti-aging vehicle natural gas catalyst according to claim 8, characterized in that: In step (1) and step (2), the drying temperature is 180-220° C., the drying time is 2.5-3.5 h, the roasting temperature is 550-650° C., and the roasting time is 1.5-2.5 h.